Analisis Hambatan Literasi dan Numerasi Siswa dalam Menyelesaikan Masalah Matematika pada Materi Persamaan Linier - Muhammad Davi Fatdilah; Dewi Purnama Sari (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2025)
This research aims to (1) Find out what the literacy and numeracy barriers are for students in solving mathematical problems in linear equations material, (2) Find out what students' literacy and numeracy barriers are in solving mathematical problems in linear equations material. The subjects in this research were 31 students in Class VII-A of SMP Negeri 1 Wampu for the 2025/2026 academic year. Data collection in this research was through written tests and interviews. The data analysis technique used the method according to Milles & Huberman. The results of the study showed that students experienced obstacles in several aspects: (1) Mathematical Literacy. Students had difficulty interpreting word problems into mathematical models. They tended to memorize procedures without understanding the meaning behind them. (2) Procedural Numeracy. Some students experienced difficulties and frequently made errors in basic calculations such as multiplication, subtraction, and division. (3) Conceptual Understanding. Students faced difficulties in understanding basic concepts and solution procedures, such as elimination and substitution. Although some students were able to solve problems correctly, they still had difficulty explaining the thought processes and reasoning behind their answers. The main obstacles were in variable modeling, arithmetic accuracy, and algebraic procedures.